Grievance Articulation and Community Reactions in the Men’s Rights Movement Online - Patrick Rafail; Isaac Freitas (Social Media + Society, 2019)
The Men’s Rights movements have grown extensively in the last four decades. Social media platforms, especially online communities, have been instrumental in the rise of the movement. Despite this, few studies have directly examined how the Men’s Rights movement frames its grievance in online spaces or analyzed community reactions to user-contributed content. To fill these gaps, we analyze 70,580 posts contributed to /r/MensRights, a large community of Men’s Rights activists on Reddit, using a combination of topic models and negative binomial regression. Our results indicate that users active on /r/MensRights have developed a core set of grievances. Due to the mechanics of Reddit, where users can upvote posts to increase their visibility, contributed content that is consistent with community norms is prominently featured. Online spaces such as /r/MensRights provide an optimal combination of self-reinforcing community norms and anonymity, providing social movements with powerful tools to expand their reach, recruit new members, and expand its political power. We argue that these dynamics apply more generally to social movement mobilization that occurs online.